Purchasing Behavior Based Consumer Segmentation on TikTok Shop in Indonesia Using K-Means - Wulan Novita Sari; Arief Wibowo (FE Program Studi Manajemen, 2026)
This study aims to analyze consumer segmentation on TikTok Shop in Indonesia based on purchasing behavior. The rapid growth of social commerce, particularly through TikTok Shop, has changed consumer shopping patterns, creating challenges for businesses in understanding diverse consumer characteristics to design effective marketing strategies.This study uses a quantitative approach with primary data collected through questionnaires distributed to TikTok Shop users in Indonesia. The variables used include Age (X1), Purchase Frequency (X2), and Type of Product Purchased (X3). The data was analyzed using the K-Means clustering method to classify consumers into homogeneous segments. The results of the study show that TikTok Shop consumers can be grouped into several different segments with different purchasing patterns, spending levels, and product preferences. These findings have practical implications for developing targeted and personalized marketing strategies